1989
DOI: 10.1055/s-0038-1651017
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Pathway Inhibitor in Elective Surgery: A Comparison with other Coagulation Inhibitors

Abstract: SummaryExtrinsic coagulation pathway inhibitor may be an important regulator of haemostasis to prevent thrombosis after tissue damage. The functional activity of this inhibitor was determined using a chromogenic substrate assay, and compared to the activities of anti thrombin, heparin cofactor II and protein C during the perioperative period of elective hip replacement (n = 28), cholecystectomy (n = 11), and vascular surgery (n = 5). Peroperatively, all the inhibitors decreased rather similarly and to the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0
2

Year Published

1991
1991
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 7 publications
2
22
0
2
Order By: Relevance
“…There have been some reports indicating that conventional open cholecystectomy is followed by a postoperative activation of blood coagulation [22,23,27]. The results of the present study clearly demonstrate that LC, despite being considered a minimally invasive procedure, also induces a significant hypercoagulable state, as shown by the modifications in most of the thrombelastographic parameters and PTT.…”
Section: Discussionsupporting
confidence: 75%
“…There have been some reports indicating that conventional open cholecystectomy is followed by a postoperative activation of blood coagulation [22,23,27]. The results of the present study clearly demonstrate that LC, despite being considered a minimally invasive procedure, also induces a significant hypercoagulable state, as shown by the modifications in most of the thrombelastographic parameters and PTT.…”
Section: Discussionsupporting
confidence: 75%
“…Following major surgery, a transient hypercoagulable state ensues that is comparable in magnitude to the degree of surgical trauma [14,20]. Hypercoagulation results from an imbalance between the coagulation and fibrinolytic activities [15,24].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative hypercoagulation has been shown to be related to the extent of surgical trauma. Sandset et al demonstrated that postoperative decreases in coagulation inhibitor levels (AT III, heparin cofactor II, extrinsic coagulation pathway inhibitor, and protein C) following hip surgery were two times greater than the decreases occurring after cholecystectomy (open) [20]. Since laparoscopic surgery minimizes surgical trauma compared to open surgery, the postoperative hypercoagulable state after laparoscopic procedures may potentially be diminished.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that TFPI levels are reduced during and after operative procedures [19]. All patients in this study received unfractionated heparin postoperatively.…”
Section: Discussionmentioning
confidence: 92%